SI Swiss Institute - Contemporary Art New York. - Godard, Jean-Luc; Monk, Jonathan; Wahler, Marc-Olivier; Swiss Institute, New York (New York : Swiss Institute, 2002)
Breuning, Olaf ; Buchanan, Roderick ; Fischer, Urs ; Gelatin ; Giacometti, Alberto ; Giorno, John ; Gordon, Janine ; Gygi, Fabrice ; Hattan, Eric ; Hersberger, Lori ; Jankowski, Christian ; Jecker, Ludovic ; Koether, Jutta ; Marshall, Maria ; Matelli, Tony ; Monk, Jonathan ; Motti, Gianni ; Parrino, Steven ; Pflumm, Daniel ; Rondinone, Ugo ; Ross, Michael ; Shaw, Jim ; Tzaig, Uri ; Westphalen, Olav ; Xhafa, Sislej
Exhibitions 2001-2002
Engels
boek
Keywords: Amerika; Zwitserland